2018
DOI: 10.1038/s41398-018-0281-9
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of independent DISC1 mutations on impaired neurite growth via decreased UNC5D expression

Abstract: The identification of convergent phenotypes in different models of psychiatric illness highlights robust phenotypes that are more likely to be implicated in disease pathophysiology. Here, we utilize human iPSCs harboring distinct mutations in DISC1 that have been found in families with major mental illness. One mutation was engineered to mimic the consequences on DISC1 protein of a balanced translocation linked to mental illness in a Scottish pedigree; the other mutation was identified in an American pedigree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 95 publications
1
27
0
1
Order By: Relevance
“…These changes underpin impaired neurite outgrowth in an UNC5Ddependent manner in vitro. All in all, findings from this [37] and previous reports [34] strengthen the hypothesis that DISC1 mutations causally impact presynaptic function in vitro. Even though, we would like to emphasize again that their relevance to common psychiatric disorders remains controversial since no additional families carrying the mutations from the original index cases have been identified so far.…”
Section: Disc1 S Role In Presynaptic Function and Neural Developmentsupporting
confidence: 86%
See 2 more Smart Citations
“…These changes underpin impaired neurite outgrowth in an UNC5Ddependent manner in vitro. All in all, findings from this [37] and previous reports [34] strengthen the hypothesis that DISC1 mutations causally impact presynaptic function in vitro. Even though, we would like to emphasize again that their relevance to common psychiatric disorders remains controversial since no additional families carrying the mutations from the original index cases have been identified so far.…”
Section: Disc1 S Role In Presynaptic Function and Neural Developmentsupporting
confidence: 86%
“…This promotes premature NPC differentiation and deletions impaired cortical layer formation. Rescue by Wnt-antagonists [37] [ 34,36] DISC1 See [34,36] Cortical glutamatergic Both mutations converge on few DEGs including UNCD5. iNS…”
Section: Esc/ipsc-based Modeling Of Structural Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data might suggest a greater propensity for the spread of αSyn pathology, but future work in animal models will be best suited to fully address the implications of this altered αSyn release. Both lysosomal deficiency and αSyn accumulation can contribute to decreased neuronal maturation in primary rodent neurons and neuronal cell culture model (Ramonet et al, 2011;Koch et al, 2015;Wrasidlo et al, 2016;Prots et al, 2018;Srikanth et al, 2018). Accordingly, we observed that GBA1 heterozygous-null iNs display a decrease in neurite length, as well as number of neurite branch points.…”
Section: Discussionmentioning
confidence: 62%
“…Thus, the processing of DISC1 in AD patients apparently varied compared to all other diseases and controls. The function and mechanisms of DISC1 in Alzheimer dementia are not clear [44][45][46][47]82]. There may be some hints about the function of DISC1 by the examination of its domain architecture (Fig.…”
Section: Disc1 Domainsmentioning
confidence: 99%